2020
DOI: 10.1039/d0ra01415j
|View full text |Cite|
|
Sign up to set email alerts
|

Preventive effect of lemon seed flavonoids on carbon tetrachloride-induced liver injury in mice

Abstract: The aim of this study was to determine the preventive effect of lemon seed flavonoids (LSF) on carbon tetrachloride-induced liver injury in mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…ALT, AST and ALP mainly exist in various tissues, such as the liver [ 25 ]. Upon liver injury, those biomarkers are released into the blood, resulting in an increase in ALT, AST and ALP levels in serum [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…ALT, AST and ALP mainly exist in various tissues, such as the liver [ 25 ]. Upon liver injury, those biomarkers are released into the blood, resulting in an increase in ALT, AST and ALP levels in serum [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Yang 41 confirmed that lemon seed flavonoids are a mixture of flavonoids, and their active substances have a protective impact on CCl 4 -induced liver damage in mice. CCl 4 can prevent abnormality in serological parameters, including liver function signals, and restore the oxidation and inflammation indices to normal.…”
Section: Resultsmentioning
confidence: 91%
“…The liver is the main metabolic organ for the metabolism of nutrient substances and detoxification of toxins. 12 Long-term exposure to exogenous toxins, including viruses, environmental toxic agents, drugs, and natural foods-derived toxins always leads to liver damage, which subsequently results in hepatitis, fibrosis, cirrhosis, and finally cancer. 13,14 The incidences of liver injuries are increasing every year.…”
Section: Introductionmentioning
confidence: 99%